Analysis of Antibiotic Drug Utilization in Pediatric Pneumonia Patients at Cilacap Regional Public Hospital Using the ATCDDD Method and DU 90% - Fiqih Nurkholis (LPPM Universitas Harapan Bangsa, 2024)
The high incidence of infectious pneumonia will increase the use of antibiotics. This disease is a leading cause of death in children under 5 years of age. This study aims to describe the utilization of antibiotics for pneumonia in pediatric patients aged ≤ 5 who were treated at RSUD Cilacap in 2022. The research method used was a descriptive study with retrospective data collection, referring to medical record data. Samples were taken using the total sampling method and evaluated using the ATC/DDD and DU 90% methods. The results showed that male pediatric patients were more prevalent (55.55%) with the highest age group being 0-1 years (40.27%). The most frequently used antibiotic was Ceftriaxone (45.06%). The highest DDD/100 bed days value was for Azithromycin at 52.14, and the lowest DDD/100 bed days value was for Metronidazole at 0.31. The antibiotic with the highest DU 90% value was Azithromycin (65.18). The results of the study can be concluded that elevated overall DDD/100 days value suggests that the greater the utilization of antibiotics within a 100-day treatment period, while the extensive inclusion of drugs in 90% DU segment indicates a less discerning approach to antibiotic selection in therapy